Implementation of Collaborative Governance-Based Waste Management Policy: Educational Perspective and Human Values (Study at the Tlekung Landfill, Batu City) - Diva Aqila Berliandy; Abdul Juli Andi Gani; Moh Said (Journal of General Education and Humanities, 2026)
The complexity of waste management in Batu City has increased due to population growth, tourism activities, shifting consumption patterns, and low public awareness of waste sorting. This study aims to analyze the implementation of waste management policies using Merilee S. Grindle’s implementation model and to evaluate the effectiveness of collaborative governance based on the framework developed by Ansell and Gash. A qualitative descriptive approach was employed, with data collected through interviews, observation, and documentation. The findings reveal that in terms of policy content, the Mayor’s Regulation has incorporated essential principles such as waste reduction from source, sorting, and community participation. Regarding collaborative governance, initial forms of collaboration have emerged among the Environmental Agency, community groups, and the private sector. However, the overall waste management system in Batu City has not yet operated effectively, both in policy implementation and multi-stakeholder collaboration. This research is expected to serve as a reference for policymakers, particularly in tourism-oriented cities, in developing more effective and sustainable waste management systems.